Illustrated technique of superficial lymphadenectomy of dogs and cats: preliminary study - do Brasil, Matheus Junger; Branco, Clara Villela Castello; Cappelli, Naomi; da Silva , Joice Bento; Rodrigues, Rosaura Leite; Fernandes, Maria Eduarda dos Santos Lopes (Brazilian Journal of Veterinary Medicine, 2024)
Superficial lymphadenectomy is an easy-to-perform and cost-effective routine technique. Despite its simplicity, it remains underutilized in veterinary medicine, with most practitioners being oncological surgeons. This study aims to enhance accessibility to the surgical procedure by providing anatomical representations of superficial lymphadenectomy in the carcasses of dogs and cats. A preliminary study involving two canines and two felines was conducted, with each group comprising a dog and a cat. Group A was designated to superficial lymphadenectomy techniques to create an illustrated step-by-step procedure, while group B underwent anatomical dissection to expose lymph nodes and their adnexa. The approach to superficial lymph nodes in dogs and cats is simple, allowing for the demonstration of superficial lymphadenectomy techniques in the corpses of dogs and cats without complications. This includes the dissection and presentation of anatomical structures adjacent to the lymph nodes. In conclusion, the techniques applied to subjects in groups A and B proved effective, successfully demonstrating and excising all superficial lymph nodes in the corpses of dogs and cats. These findings suggest that the developed set of techniques developed for lymph node excision holds promise for safe and effective application in live animals.